Fault detection and isolation analysis and design for solution copolymerization of MMA and VAc process. Issue 4 (11th November 2015) - Shahnazari, Hadi; Mhaskar, Prashant
Abstract : The problem of detecting and isolating distinguishable actuator and sensor faults in the solution copolymerization of methyl methacrylate and vinyl acetate monomers are considered in this work. To this end, first state estimates are generated using a bank of high‐gain observers, and nonlinear fault detection and isolation (FDI) residuals are defined. The process dynamics are further analyzed to categorize fault scenarios as distinguishable and indistinguishable, and the necessary and sufficient conditions for the classification are presented. Subsequently, filters are designed that enable FDI for the distinguishable fault scenarios, with the advantage of detecting and confining possible locations for indistinguishable faults. The FDI filters are implemented on the copolymerization process, and the results compared with a linear model based filter design. © 2015 American Institute of Chemical Engineers AIChE J, 62: 1054–1064, 2016